Legal Certainty in Peace Agreements in Default Disputes Through Negotiations - harisman harisman; Mhd Yadi Harahap; fauziah lubis (Universitas Muhammadiyah Sumatera Utara, 2023)
This study aims to analyze the legal certainty of a settlement agreement on a default dispute through negotiation. The desire to resolve the default dispute through negotiations is stated in a peace agreement. In order for the peace agreement to be effective, it is necessary to look at the legal certainty aspect. For this reason, a research was conducted with a normative juridical approach and using secondary data sourced from the literature. Secondary data were analyzed qualitatively and the results were described. Based on the analysis, it was found that the peace agreement in the negotiation is categorized as one type of agreement which is subject to the provisions of the Civil Code and Law Number 30 of 1999 concerning Arbitration and Alternative Dispute Resolution. Legal certainty and the legal force of a breach of contract peace agreement through negotiation are obtained from the implementation of Article 1338 paragraph (1) of the Civil Code relating to the principle of pacta sun servanda and Article 1858 of the Civil Code, as well as the formal requirements for a peace agreement to be in writing